2021
DOI: 10.1098/rsbl.2020.0833
|View full text |Cite
|
Sign up to set email alerts
|

Detecting flying insects using car nets and DNA metabarcoding

Abstract: Monitoring insects across space and time is challenging, due to their vast taxonomic and functional diversity. This study demonstrates how nets mounted on rooftops of cars (car nets) and DNA metabarcoding can be applied to sample flying insect richness and diversity across large spatial scales within a limited time period. During June 2018, 365 car net samples were collected by 151 volunteers during two daily time intervals on 218 routes in Denmark. Insect bulk samples were processed with a DNA metabarcoding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The measurements of the net were as follows: front height: 75 cm; front width: 100 cm; length: 140 cm; width of sampling bag: 29 cm; mesh size at the bottom (grey fabric): 2 × 1 mm; and mesh size for the rest of the net (white fabric): ~0.3 mm. Custom tent poles (L: 209 cm, D: 8 mm) supported the opening of the net (see also Supplementary Information in Svenningsen et al (2021)).…”
Section: Methodsmentioning
confidence: 76%
“…The measurements of the net were as follows: front height: 75 cm; front width: 100 cm; length: 140 cm; width of sampling bag: 29 cm; mesh size at the bottom (grey fabric): 2 × 1 mm; and mesh size for the rest of the net (white fabric): ~0.3 mm. Custom tent poles (L: 209 cm, D: 8 mm) supported the opening of the net (see also Supplementary Information in Svenningsen et al (2021)).…”
Section: Methodsmentioning
confidence: 76%
“…Citizens have also helped to compile the training data needed for machine learning, for example, in the PollinatorWatch project (https:// www.zooniverse.org/projects/tokehoye/pollinatorwatch). In projects using DNA technology, some rely on citizen scientists for the collection of the insect samples [105], which are subsequently processed by scientists. A few citizen science projects are starting to include citizens in the analysis steps (e.g., the DNA&life project in Denmark) [106].…”
Section: Molecular Methodsmentioning
confidence: 99%
“…Imbedded in the original development of DNA barcoding was, however, an essential subgoal to build a reference library where quality-checked, named specimens identified by means of classical morphological methods and deposited in voucher collections are linked to their barcodes and so-called barcode index numbers (BINs) [18]. So far, rather modest funding and efforts have been allocated to this endeavor while more and more studies uncritically use BINs to represent proxies for species [19] or uncritically extract names from the Barcode of Life online database BoldSystems (BOLD) and GenBank without validating their sources and quality [20,21]. For instance, Svenningsen et al [20], in a study detecting flying insects using car nets and DNA metabarcoding, claimed they documented 319 species not previously known from Denmark.…”
Section: Figure 3 Google Ngrammentioning
confidence: 99%
“…So far, rather modest funding and efforts have been allocated to this endeavor while more and more studies uncritically use BINs to represent proxies for species [19] or uncritically extract names from the Barcode of Life online database BoldSystems (BOLD) and GenBank without validating their sources and quality [20,21]. For instance, Svenningsen et al [20], in a study detecting flying insects using car nets and DNA metabarcoding, claimed they documented 319 species not previously known from Denmark. When checking the species of Mycetophilidae on their list, it was found that all five species claimed new to Denmark were not new but appeared new due to misspellings, synonyms, and different genus combinations.…”
Section: Figure 3 Google Ngrammentioning
confidence: 99%